(untitled) (Eurasian Journal of Philology Science and Education, 2016)
Semantic as linguistic discipline is determined by linguistics of text, from one side, and progmatika withother. In the article some aspects consisting in the followingare studied: semantics is distinguished as a maincom ponent is in the structure of expression, designated by language signs. A sing has bilateral essence, and one ofhis parties is presented exactly by a value. Therefore the value plugged in semantic spieces all system of language, and a language is indendedfor communication of senses and their values, and all hisunits are provided with a value and serves the meaning fulements used in text. Scientists distinguish a dictionary and his basic units as a starting point, which in the languages of in flexional type, for example, of Russian, there are words of lexeme. Words possess formal valencies; when these valencies will be realized, then before us arephrases. Their elements are signs and constructions, there are difficult signs, but comformities to law of their forming and functioning at this aspect of consideration are determinedby formal properties of words and constructions. The word speculiarto along with formal, and rich in content valencies as a source of semantic limitations, i.e. it is ability of words of enter in on or another constructions, and also support for establishment of semantic interpretation of constructi onsand expressions build on their basis.